2011
DOI: 10.1186/2191-1991-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring economic consequences of preterm birth - Methodological recommendations for the evaluation of personal burden on children and their caregivers

Abstract: This study aims to identify the impact of a preterm birth on financial and emotional burden from the families' perspective. Additionally, a comprehensive schedule of recommendations for a sufficient evaluation of all aspects of burden is developed. Based on the results of a literature search relevant categories and sub-domains for a questionnaire covering multiple aspects of associated financial and emotional burden are identified and converted into a recommendation scheme. Results of the literature search ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 45 publications
5
84
0
Order By: Relevance
“…The cost of caring for individual infants varies according to their gestational age [18], with care for an extremely preterm infant reaching ~US$250,000 [10]. …”
Section: Preterm Birthmentioning
confidence: 99%
“…The cost of caring for individual infants varies according to their gestational age [18], with care for an extremely preterm infant reaching ~US$250,000 [10]. …”
Section: Preterm Birthmentioning
confidence: 99%
“…Increases in morbidity related to low birth weight (LBW) contributes to high direct medical costs, 2528 non-medical costs such as higher child care expenses, 29 and less tangible costs such as the burden of caregiving to families. 30,31 Recent studies using national data sets have identified linkages between general LHD spending and broad, distal mortality outcomes and related disparities. 32,33 Based on these studies and another indicating that MCH-specific services provided by LHDs are linked to reductions in mortality disparities, 2 this study used unique, detailed data obtained through a two-state consortium of Public Health Practice-Based Research Network (PBRN) partners to examine impacts of MCH-related spending by LHDs on birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In addition, LBW is considered as a universal threat for developing countries that creates a barrier for child development. 8,9 Other studies have shown several factors to be determinants of LBW and have demonstrated that preventing those factors can help reduce early childhood morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, with the demographic change of increased life expectancy at birth in developing countries, children born with LBW can cause an increased economic burden and an increased disease burden. 6,7 In addition, LBW is considered as a universal threat for developing countries that creates a barrier for child development.…”
Section: Introductionmentioning
confidence: 99%